EVALUASI IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH MIN 12 MEDAN - Surya Kartini Indah Sari Siregar, Nur Azizah Siregar, M. Taufik Hidayat Lubis, Rahma Maulida Rambe (CV. Adiba Aisha Amira, 2024)
This research aims to evaluate the implementation of the Merdeka Curriculum at the MIN 12 Medan School. The method used is mixed methods with a survey approach and in-depth interviews with teachers to collect quantitative data. In-depth interviews were conducted to obtain more detailed qualitative data. The research results show that although there are challenges in teacher readiness and understanding as well as limited resources, support from continuous training and the use of digital learning resources can increase the effectiveness of curriculum implementation. Research recommendations include strengthening mentoring by experienced facilitators and developing learning communities. This research provides a comprehensive overview of the obstacles and solutions in implementing the Independent Curriculum in elementary schools.